An optimization procedure of shape and position of the aerodynamic device at the rear side of a semi-trailer truck model - Stjepan Galamboš; Nebojša Nikolić; Goran Vorotović; Boris Stojić; Jovan Dorić; Dalibor Feher (Heliyon)
The paper outlines the development and optimization of an aerodynamic device for a semi-trailer truck model to reduce aerodynamic drag force. The optimization procedure involves the selection of a basic aerodynamic device shape, using airfoil profiles, and refining its shape and position through established optimization techniques like Full Factorial Design and Response Surface Method within the Design of Experiments framework. The test subject is a 1:10 scale model of the semi-trailer truck. To validate the results obtained from the Computational Fluid Dynamics (CFD) simulations, experimental measurements of aerodynamic drag forces were performed in a wind tunnel. This combination of simulation and experimental testing ensures the reliability and effectiveness of the optimization process for improving vehicle aerodynamics.